VP1 Amino Acid Residue 145 of Enterovirus 71 Is a Key Residue for Its Receptor Attachment and Resistance to Neutralizing Antibody during Cynomolgus Monkey Infection - Fujii, Ken; Sudaka, Yui; Takashino, Ayako; Kobayashi, Kyousuke; Kataoka, Chikako; Suzuki, Tadaki; Iwata-Yoshikawa, Naoko; Kotani, Osamu; Ami, Yasushi; Shimizu, Hiroyuki; Nagata, Noriyo; Mizuta, Katsumi; et al. (Journal of virology, 2018)
The contribution of VP1-145 variants in humans is not fully understood. In some studies, VP1-145G/Q viruses were isolated more frequently from severely affected patients than from mildly affected patients, suggesting that VP1-145G/Q viruses are more virulent. In the accompanying paper (K. Kobayashi, Y. Sudaka, A. Takashino, A. Imura, K. Fujii, and S. Koike, J Virol 92:e00681-18, 2018, https://doi.org/10.1128/JVI.00681-18 ), we showed that VP1-145E viruses are more virulent than VP1-145G viruses in human SCARB2 transgenic mice. Heparan sulfate acts as a decoy to specifically trap the VP1-145G viruses and leads to abortive infection. Here, we demonstrated that VP1-145G was attenuated in cynomolgus monkeys, suggesting that this hypothesis is also true in a nonhuman primate model. VP1-145E viruses, but not VP1-145G viruses, were highly resistant to neutralizing antibodies. We propose the difference in resistance against neutralizing antibodies as another mechanism of EV71 virulence. In summary, VP1-145 contributes to virulence determination by controlling attachment receptor usage and antibody sensitivity. Enterovirus 71 (EV71) is a causative agent of hand, foot, and mouth disease and sometimes causes severe or fatal neurological complications. The amino acid at VP1-145 determines the virological characteristics of EV71. Viruses with glutamic acid (E) at VP1-145 (VP1-145E) are virulent in neonatal mice and transgenic mice expressing human scavenger receptor B2, whereas those with glutamine (Q) or glycine (G) are not. However, the contribution of this variation to pathogenesis in humans is not fully understood. We compared the virulence of VP1-145E and VP1-145G viruses of Isehara and C7/Osaka backgrounds in cynomolgus monkeys. VP1-145E, but not VP1-145G, viruses induced neurological symptoms. VP1-145E viruses were frequently detected in the tissues of infected monkeys. VP1-145G viruses were detected less frequently and disappeared quickly. Instead, mutants that had a G-to-E mutation at VP1-145 emerged, suggesting that VP1-145E viruses have a replication advantage in the monkeys. This is consistent with our hypothesis proposed in the accompanying paper (K. Kobayashi, Y. Sudaka, A. Takashino, A. Imura, K. Fujii, and S. Koike, J Virol 92:e00681-18, 2018, https://doi.org/10.1128/JVI.00681-18 ) that the VP1-145G virus is attenuated due to its adsorption by heparan sulfate. Monkeys infected with both viruses produced neutralizing antibodies before the onset of the disease. Interestingly, VP1-145E viruses were more resistant to neutralizing antibodies than VP1-145G viruses in vitro . A small amount of neutralizing antibody raised in the early phase of infection may not be sufficient to block the dissemination of VP1-145E viruses. The different resistance of the VP1-145 variants to neutralizing antibodies may be one of the reasons for the difference in virulence. IMPORTANCE The contribution of VP1-145 variants in humans is not fully understood. In some studies, VP1-145G/Q viruses were isolated more frequently from severely affected patients than from mildly affected patients, suggesting that VP1-145G/Q viruses are more virulent. In the accompanying paper (K. Kobayashi, Y. Sudaka, A. Takashino, A. Imura, K. Fujii, and S. Koike, J Virol 92:e00681-18, 2018, https://doi.org/10.1128/JVI.00681-18 ), we showed that VP1-145E viruses are more virulent than VP1-145G viruses in human SCARB2 transgenic mice. Heparan sulfate acts as a decoy to specifically trap the VP1-145G viruses and leads to abortive infection. Here, we demonstrated that VP1-145G was attenuated in cynomolgus monkeys, suggesting that this hypothesis is also true in a nonhuman primate model. VP1-145E viruses, but not VP1-145G viruses, were highly resistant to neutralizing antibodies. We propose the difference in resistance against neutralizing antibodies as another mechanism of EV71 virulence. In summary, VP1-145 contributes to virulence determination by controlling attachment receptor usage and antibody sensitivity.